Are rules and boundaries sufficient to limit harmful central bank discretion? Lessons from Europe - Athanasios Orphanides (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2014)
Marvin Goodfriend's (2014) insightful, informative and provocative work explains concisely and convincingly why the Fed needs rules and boundaries. This paper reviews the broader institutional design problem regarding the effectiveness of the central bank in practice and confirms the need for rules and boundaries. The framework proposed for improving the Fed incorporates key elements that have already been adopted in the European Union. The case of ELA provision by the ECB and the Central Bank of Cyprus to Marfin-Laiki Bank during the crisis, however, suggests that the existence of rules and boundaries may not be enough to limit harmful discretion. During a crisis, novel interpretations of the legal authority of the central bank may be introduced to create a grey area that might be exploited to justify harmful discretionary decisions even in the presence of rules and boundaries. This raises the question how to ensure that rules and boundaries are respected in practice.
urn:nbn:de:hebis:30:3-361092
Keywords: E58; E61; 330; Rules; discretion; central bank mandates; ECB; Central Bank of Cyprus; ELA